Measurements of dynamic surface strains induced by blasting near a highwall of a coal mine – a preliminary assessment - Henley, KN; Spathis, AT (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Five production blasts at a coal mine were monitored at the top of the highwall using multiple vibration monitors from which the two dimensional transient surface strains were inferred using a novel analysis method. The rock type at the top of the highwall was semi-consolidated sediments typical of natural surface cover in central Queensland coal mines. The monitors were located between 81 and 280 metres from the production blasts, and approximately 10 m from the highwall crest. Vibration levels recorded were between 50 and 226 mm/s, while maximum tensile principal strains were between 123 and 542 microstrain. No obvious surface cracks were noted at the monitoring location.